THE ISSUE OF MAN AS PER SUFI VIEWS OF AZIZIDDIN NASAFI (American Journal of Research in Humanities and Social Sciences, 2025)
In the following article the sufi views of the Aziziddin Nasafi is analysed based on his teachings on perfect man. In the process of analyzing this article, methods of logic, historicity, consistency and objectivity of scientific knowledge were widely used. The true nature of the concept of perfect man was illuminated in logical consistency.